The Chicago Review Press NCLEX RN practice test and review - Waide, Linda; Roland, Berta (NCLEX Practice Test and Review series., 2004)
Fully revised to conform to the 2004 NCLEX Test Plan, this study guide and test includes hot spot, fill-in-the-blank, and select-all-that-apply questions to reflect the new test format. Ten written practice tests cover all the body systems and two additional practice tests cover mental health and miscellaneous topics. Each practice test includes a system overview and complete explanations for both correct and incorrect answers. In addition to the written tests, a 100-item interactive software CD in the NCLEX format is included to allow students to become comfortable with the on-screen exam.